Primeiro censo dos moradores de rua da cidade de São Paulo procedimentos metodológicos e resultados - Schor, Silvia Maria (2001)
The article presents the methodological procedures and the results of the first homeless population census of the city of São Paulo, held in 2000. The data collected through the census required the development of a peculiar methodology as the population in question has no address, is spatially spread all over the city and mostly noticed during the night. The data concerning the spatial distribution ofthe population, gender, color and age are presented, considering the homeless people found at shelters and at parks, streets, squares and other public spaces.